2011
DOI: 10.1186/1477-7819-9-107
|View full text |Cite
|
Sign up to set email alerts
|

The association of fish consumption with bladder cancer risk: A meta-analysis

Abstract: BackgroundThe association between fish consumption and risk of bladder cancer has not been established yet. The results from epidemiological studies are inconsistent.MethodsWe conducted a meta-analysis of cohort and case-control studies on the relationship between fish intake and bladder cancer. We quantified associations with bladder cancer using meta-analysis of relative risk associated to the highest versus the lowest category of fish intake using random effect models. Heterogeneity among studies was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A possible explanation lies in some Mediterranean diet components that may decrease postprandial oxidative levels, which are responsible for acute inflammation state [ 41 , 42 , 43 ]. With reference to other dietary factors considered in the development of the MDS, no clear associations with bladder cancer were reported for fish [ 44 ], alcohol [ 45 ], milk/dairy products [ 46 ], or meat [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation lies in some Mediterranean diet components that may decrease postprandial oxidative levels, which are responsible for acute inflammation state [ 41 , 42 , 43 ]. With reference to other dietary factors considered in the development of the MDS, no clear associations with bladder cancer were reported for fish [ 44 ], alcohol [ 45 ], milk/dairy products [ 46 ], or meat [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analysis of five cohort studies resulted in a pooled RR of 0.84 (95% CI, 0.42–1.26) and meta‐analysis of nine case‐control studies resulted in a pooled non‐significant RR of 0.87 (95% CI, 0.54–1.21) (Li et al . ). Previously, WCRF/AICR had concluded that there was limited evidence for an association between fish consumption and bladder cancer but that no conclusion could be drawn (WCRF & AICR ).…”
Section: Cardiovascular Diseasementioning
confidence: 97%
“…smokingI 2  = 28.5Egger p  = 0.051Boyle et al [30]Sweetened carbonated beverages5 studiesHigh versus lowYesRR 1.13; 95 % CI 0.89–1.455I 2  = 0.0 %Egger p  = 0.05Li et al [135]MilkDairy products12 CC6 COHMilk; high versus lowYesRRm = 0.91; 95 % CI 0.72–1.157Most adjustedQ p  = 0.020Egger p  = 0.048Dairy products; high versus lowYesRRm = 1.01; 95 % CI 0.86–1.193Most adjustedQ p  = 0.108Egger p  = 0.73Mao et al [31]Milk and Dairy products8 HCC5 PCC6 COHAll milk; high versus lowNoRRms = 0.84; 95 % CI 0.72–0.9716Most adjusted, incl. smokingI 2  = 70.1 %Egger p  = 0.055Whole milk; high versus lowNoRR 2.23; 95 % CI 1.45–3.002I 2  = 0Skim milk; high versus lowNoRR 0.47; 95 % CI 0.18–0.792I 2  = 0Fermented milk; high versus lowNoRR 0.69; 95 % CI 0.47–0.915I 2  = 62.5 %Li et al [32]Fish6 HCC…”
Section: Appendixmentioning
confidence: 99%